1982
DOI: 10.1007/bf00283746
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein cholesterol: An association with the severity of diabetic retinopathy

Abstract: Summary. Diurnal profiles of total and lipoprotein cholesterol and triglycerides were measured in 11 insulin-dependent diabetic subjects without retinopathy, 10 with background and 10 with proliferative retinopathy. The groups were closely matched for age and duration of diabetes. Total cholesterol levels were higher in patients with proliferative (5.6_+ 0.5mmol/1) than background (5.1 + 0.7mmol/1) or no retinopathy (4.6_+ 0.8mmol/1, trend test; p < 0.003), due to raised levels of low density lipoprotein (LDL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
3

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 22 publications
5
37
3
Order By: Relevance
“…Dornans group did not find any relationship between serum triglyceride levels and severity of retinopathy in insulindependent diabetic patients (Dornan et al 1982) and a study by Agardh (1988), gave the same results. On the other hand, Weber et al found that serum triglycerides were strongly associated with degree of retinopathy in children and adolescents with diabetes mellitus type 1 (Weber et al 1986).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Dornans group did not find any relationship between serum triglyceride levels and severity of retinopathy in insulindependent diabetic patients (Dornan et al 1982) and a study by Agardh (1988), gave the same results. On the other hand, Weber et al found that serum triglycerides were strongly associated with degree of retinopathy in children and adolescents with diabetes mellitus type 1 (Weber et al 1986).…”
Section: Discussionmentioning
confidence: 80%
“…Serum cholesterol levels were in some studies found to correlate to more severe retinopathy (Dornan et al 1982;Eckel et al 1981;Mouton & Gill 1988 ;Scanu & Fless 1990;Weber et al 1986) while in other studies such a relationship was not found (Weber et al 1986;West et al 1980). Dornan et al (1982) measured serum lipid levels in small groups of insulin-dependent diabetic patients and controls. They found higher levels of total cholesterol with more severe retinopathy; no association with high density lipoprotein levels and degree of retinopathy; and decreasing HDL/LDL ratio with more severe retinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Further studies have linked LDL cholesterol with maculopathy, although numbers of patients in these studies are small. 18,19 A direct toxic effect of LDL on retinal capillary pericytes has also been demonstrated, and this toxic effect can be enhanced by LDL glycation or oxidation. In other small cross-sectional studies, lipoprotein (a) has been suggested as a risk factor for maculopathy, 20,21 although this finding is refuted on examination of a small subset of the WESDR population.…”
Section: Are Serum Lipids Associated With Increased Risk Of Maculopathy?mentioning
confidence: 99%
“…It is not possible to define which diabetic individuals will present retinopathy. However, it is possible to determine risk factors related to the development of retinopathy (5) , such as duration of systemic disease, poor diabetes control, insulin-dependent diabetes, dislipidemia, hypertension, alcoholism, pregnancy, associated renal disease, anemia hypomagnesemia and African descendant (1,(8)(9)(10)(11)(12)(13)(14)(15)(16) . Some studies suggest that retinopathy progression is almost inexistent in younger-onset diabetics (less than 13 years-old).…”
Section: Introductionmentioning
confidence: 99%